Deskripsi Kemampuan Komunikatif dan Kolaboratif Mahasiswa Pendidikan Biologi Melalui Penerapan Model Pembelajaran Project Based Learning - Titin, Titin; Wahyuni, Eko Sri; Komaria, Siti; Ayu, Nambisas Arum Kusuma; Wilma, Wilma (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
This research was conducted using descriptive research methods. This method was chosen to describe the communicative and collaborative abilities of Biology Education students through the application of the Project Based Learning (PjBL) model. The research stages are adapted to a model consisting of 6 stages, namely determining the project, planning steps to complete the project, preparing a schedule for implementing the project schedule, implementing the project with lecturer monitoring, preparing reports and publishing project results, and evaluating the implementation of activities, as well as the final results of the project. The research instrument used in this research is a questionnaire to measure communicative and collaborative abilities which was completed by 64 Biology Education student respondents, Faculty of Teacher Training and Education, Tanjungpura University. The results of the analysis of the communicative questionnaire which is composed of 6 aspects, obtained aspects of task presentation 88% in the very good category, asking questions 58% in the sufficient category, responding to presentation results 92% in the very good category, discussion 89% in the very good category, cooperation in groups 89% in the very good category, and decision making 76% in the good category. Meanwhile, the results of the collaborative questionnaire analysis showed that the group contribution aspect was 95% in the very good category, mutual assistance was 64% in the sufficient category, and flexibility was 95% in the very good category. From these results it was found that the average for each communicative and collaborative questionnaire was respectively 76% in the good category and 84.7% in the very good category. So it can be concluded that the application of the Project Based Learning (PjBL) model can improve students' communicative and collaborative abilities in the learning process.